Gambaran Gejala Klinis Demam Berdarah Dengue pada Anak di RSUP Sanglah, Denpasar Selama Bulan Januari-Desember 2013 - Khadijah, Andi Nurul; Lingga Utama, I Made Gede Dwi (E-Jurnal Medika Udayana, 2017)
Dengue Hemorrhagic Fever is an infectious disease commonly found in the tropics and is an acute dengue fever that affects children with clinical manifestations of bleeding and causes shock which can result in death. The case fatality rate of dengue fever can reach more than 20%, most cases are children. This study aims to determine the clinical picture of DF, DHF and DSS, where the clinical picture is one of the determinants of the diagnosis. This study is a descriptive study with cross-sectional design and retrospective approach. The data obtained in this study is secondary data in the form of medical records of pediatric patients treated in Pediatric Intensive Care Unit (PICU). Pudak and Jempirimg wards period January to December 2013. Data processing is done by descriptive analysis using statistical software that is SPSS version 20. It was found that the dominant clinical picture (5 clinical features) in DF patients was fever (78.94%), vomiting (47.36%), decreased appetite (31.57%), nausea (26.31%), and abdominal pain (26.31%). In DHF patients, the dominant clinical symptoms were fever (100%), vomiting (58.33%), abdominal pain (54.17%), nausea (41.67%), decreased appetite and drinking (37.5%), Headache, and tourniquet test. In the DSS patients, the dominant clinical symptoms were vomiting (84.61%), fever (76.92%), cold hands and feet / extremities (53.8%), CRT ? 2 seconds and abdominal pain (46.15%), As well as a weak pulse (38,46 %). Keyword: DF, DHF, DSS, Clinical Manifestation, Platelet, Hematrocrit.